Fast Food Restaurants and Convenience Stores: Using Sales Volume to Explain Crime Patterns in Seattle. (December 2018) - Askey, Amber Perenzin; Taylor, Ralph; Groff, Elizabeth; Fingerhut, Aaron
This study investigates how convenience stores and fast food restaurants influence crime patterns over time. Using sales volume data from fast food restaurants and convenience stores, we examine streetblock crime levels over a seven year period in Seattle using multilevel models. Results demonstrate that high sales volume links to high crime, even after controlling for local socio-economic status, the effects of retail businesses, and local crime trends. In addition, street segment crime trajectories were spatially clustered in a significant way. The dynamics that explain why specific types of commercial facilities link to street crime need further theoretical clarification. This is the first study demonstrating significant spatio-temporal patterning of streetblock crime trends.